The role of chamber system in development of agricommerce in Serbia - Cukic, Emil (Applied Studies in Agribusiness and Commerce, 2010)
This research is carried out in order to be determined the role of Chamber system in development of agricommerce along with successful preparation of Serbia for EU accession. On February 28, 1857 Prince Aleksandar Karaðorðeviæ signed the Decree, called THE CONSTITUTION OF THE TRADE. By this Decree, the first BusinessAssociation in Serbia was constituted. Under the Law on retail stores passed in June 1910, the first chambers were established. Those were the following: • The Chamber of TRADE • The Chamber of CRAFTS • The Chamber of INDUSTRY • The Chamber ofWORKERSToday, in conditions of economic and social reforms and transfer toward market oriented economy, chambers in Serbia chose to reconsider their role, by using experiences of chambers in countries with developed market economy.The chamber strives to be organized as independent, business oriented and expert association of economic operators. The structure of economy, from the aspect of important economic indicators (total revenue, profit), shows dominant share of manufacturing andagro-industry, trade, financial and other services sectors, transport, telecommunication, and construction industries. By generating over 30% of GDP and employment, Belgrade plays vital role in the economy of the whole Serbia. That is an advantage, but also the responsibility to constantly stimulate faster development and higher living standards by inciting the positive changes in economic and overall environment.